Optical Studies in Red/NIR Persistent Luminescent Cr-Doped Zinc Gallogermanate (ZGGO:Cr) - Maria S. Batista; Joana Rodrigues; Maria S. Relvas; Júlia Zanoni; Ana V. Girão; Ana Pimentel; Florinda M. Costa; Sónia O. Pereira; Teresa Monteiro (Applied Sciences, 2022)
Zn1+xGa2−2xGexO4 (ZGGO:Cr)-persistent phosphor, with a molar fraction, x, of x = 0.1, doped with a 0.5% molar of chromium, was synthesised via solid-state reaction at 1350 °C for 36 h. X-ray diffraction measurements and Raman spectroscopy evidence a single crystalline phase corresponding to the cubic spinel structure. Room temperature (RT) photoluminescence (PL) and afterglow decay profiles were investigated using above and below bandgap excitation. In both cases, persistent PL was observed for almost 8 h, mainly originating from a Cr3+ defect, the so-called N2 optical centre. RT PL excitation and diffuse reflectance allow identification of the best pathways of Cr3+ red/NIR emission, as well as estimation of the ZGGO bandgap energy at 4.82 eV. An in-depth investigation of the observed luminescence at 15 K and temperature-dependent PL under site-selective excitation reveals the spectral complexity of the presence of several optically active Cr3+ centres in the ZGGO host that emit in almost the same spectral region. Furthermore, the temperature dependence of the R-lines’ intensity indicates the existence of thermal populating processes between the different optical centres. Such observations well account for a wide distribution of defect trap levels available for carrier capture/release, as measured by the persistent luminescence decay, from which the carriers are released preferentially to the N2 Cr3+-related optical centre.